Bacterial abundance and co-acclimation in mangrove rhizosphere and non-rhizosphere soils under pyrene stress - Wang, Han; Elyamine, Ali Mohamed; Liu, Mengtong; Shi, Hongge; Wang, Rong; Zhang, Hongzhou; Qi, Junfeng; Li, Wansen (Frontiers in Microbiology, 2026)
In mangrove ecosystems, research on bacterial abundance in the rhizosphere and the non-rhizosphere soils remains limited. Moreover, the variation in bacterial taxonomy during the acclimation of sediment samples subjected to high-molecular-weight (HMW) organic pollutant stress remains poorly understood. This study was conducted in both rhizosphere and non-rhizosphere soils at depths ranging from 0 to 20 cm in the coastal mangrove of Yunxiao to evaluate the diversity and abundance of the bacterial community and to characterize the profile of its variation arising during acclimation under pyrene stress. Rhizosphere sediments were defined as those directly adhering to the roots of mangrove plants, while non-rhizospheres were those collected 3 m away from the roots. Each sample was divided into two groups: the first group was stored at 4 °C for the determination of the physicochemical characteristics of the sediments, and the second group, used for DNA analysis, was stored at −20 °C. A DNA isolation kit was used to extract total genomic DNA from the samples before and after acclimation. Polymerase Chain Reaction (PCR) amplification of the 16S rRNA genes targeting the V3-V4 region was performed. The results of this study showed that although the physicochemical properties of both rhizosphere and the non-rhizosphere sediments were unevenly distributed, no significant difference in bacterial abundance between the two zones was observed. Moreover, the abundance at 0–10 cm depth was significantly higher in both rhizosphere and non-rhizosphere sediments. The acclimation process revealed that pyrene significantly impacted bacterial community composition and abundance. In total, 23 genera were identified in the first transfer (G1), dominated by Burkholderia (23.9% vs. 9.23%), Rhodobacter (4% vs. 10.95%), Bacillus (11% vs. 10%), Xanthobacter (6.82% vs. 7.62%), Dyella (4.9% vs. 7%), Pseudomonas (6% vs. 7.70%), and Acinetobacter (5% vs. 8.63%) in non-rhizosphere vs. rhizosphere samples, respectively. Overall, the findings indicate that bacterial abundance in the rhizosphere and non-rhizosphere of mangrove ecosystems may differ from that in terrestrial plants and that the acclimation of functional bacteria could be an effective means of adapting bacterial communities to environmental disturbances.